Facile synthesis of peanut-like Sn-doped silica nano-adsorbent for affinity separation of proteins. Issue 8 (8th February 2022) - Gao, Mochou; Liu, Qin; Xue, Yuanyuan; Li, Bao; Liu, Xingchi; Shi, Zhenzhu; Liu, Nan; Zou, Xueyan
Abstract : Peanut-like Sn-doped hollow silica adsorbent is prepared in a facile method, which exhibits a specific adsorption, a high binding capacity, good recycle performance and high recovery to the GST-tagged proteins. Abstract : A peanut-like hollow silica (denoted as p-l-hSiO2 ) adsorbent is prepared in a facile method, which is composed of several silica nanospheres and has an average diameter of 22 nm, with thickness of 5 nm. Its Brunauer–Emmett–Teller (BET) surface area, pore volume and pore size are 258.9 m 2 g −1, 1.56 cm 3 g −1 and 3.9 nm, respectively. Then the afforded p-l-hSiO2 /GSH adsorbent is applied to purify glutathione S-transferases-tagged (denoted as GST-tagged) proteins. It is found that the p-l-hSiO2 adsorbent exhibits a specific adsorption, a high binding capacity (6.80 mg g −1 ), good recycling performance and high recovery (90.1%) to the target proteins, showing promising potential for the affinity separation of GST-tagged proteins.